2017
DOI: 10.1016/j.bbagen.2017.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expression of Intrepicalcin from the scorpion Vaejovis intrepidus and its effect on skeletal ryanodine receptors

Abstract: Background Scorpion venoms contain toxins that modulate ionic channels, among which are the calcins, a small group of short, basic peptides with an Inhibitor Cystine Knot (ICK) motif that target calcium release channels/ryanodine receptors (RyRs) with high affinity and selectivity. Here we describe the heterologous expression of Intrepicalcin, identified by transcriptomic analysis of venomous glands from Vaejovis intrepidus. Methods Recombinant Intrepicalcin was obtained in Escherichia coli BL21-DE3 (peripla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Intrepicalcin is a proven active calcin. It was heterologously expressed and shown to be active on RyRs [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intrepicalcin is a proven active calcin. It was heterologously expressed and shown to be active on RyRs [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, on the basis of minimum radius and electrostatic surface potential, exit 1 may form the most likely exit pathway for Ca 2+ ions. In vejocalcin and intrepicalcin, two calcins with the highest degree of subconductance (2,14), Lys 30 is replaced with a neutral Gln and Lys 22 is replaced by Ser (fig. S5), which likely lowers the energetic barriers through multiple exits, explaining the higher subconductance.…”
Section: Subconductance Is the Results Of An Extended Permeation Pathwaymentioning
confidence: 99%
“…Unlike other ion channels targeted by peptide toxins, RyRs are not exposed on the extracellular surface, yet calcins can efficiently reach them by permeating the plasma membrane (8,9). Upon engaging the RyR, calcins cause long-lived subconductance states, which are readily detected in single-channel recordings as decreased current levels at 20 to 60% of the full conductance (2,(10)(11)(12)(13)(14). The mechanism by which calcin binding results in subconductance, and how the subconductance level depends on the calcin's specific amino acid composition, had remain unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…Ion channels are the main targets of scorpion toxins. Studies have demonstrated that scorpion toxins can modulate the gating kinetics of many ion channels, including voltage-gated potassium channels (K v channels) [ 8 ], voltage-gated sodium channels (VGSCs) [ 7 , 9 ], voltage-gated calcium channels (Ca v channels) [ 10 ], chloride channels [ 11 ], and ryanodine receptors [ 12 ]. Due to their high affinity and selectivity, scorpion toxins are widely used as tools to explore the gating mechanism of ion channels [ 13 ] and their downstream cellular signaling pathways [ 14 ].…”
Section: Introductionmentioning
confidence: 99%